Adjunctive dietary intervention for bipolar disorder: a randomized, controlled, parallel‐group, modified double‐blinded trial of a high n‐3 plus low n‐6 diet. (2nd August 2021) - Saunders, Erika F. H.; Mukherjee, Dahlia; Myers, Tiffany; Wasserman, Emily; Hameed, Ahmad; Bassappa Krishnamurthy, Venkatesh; MacIntosh, Beth; Domenichiello, Anthony; Ramsden, Christopher E.; Wang, Ming
Abstract: Objective: To investigate the preliminary efficacy of a high n‐3 plus low n‐6 (H3‐L6) dietary intervention in improving mood stability in Bipolar Disorder (BD) when compared to dietary intervention with usual U.S. levels of n‐6 and n‐3 polyunsaturated fatty acid (PUFA) intakes (control diet, CD). Methods: This 2‐arm, parallel‐group, randomized, modified double‐blind, controlled 48‐week study of 12‐week intensive diet intervention in subjects with BD was conducted at a single suburban‐rural site in the mid‐Atlantic region. Participants with DSM‐IV TR BD I or II with hypomanic or depressive symptoms were randomized, stratified on gender ( N  = 82). The intervention included the provision of group‐specific study foods and dietary counseling. Variability of mood symptoms was measured by a twice‐daily, 12‐week ecological momentary analysis (EMA) paradigm, and group differences were analyzed using multilevel models. Circulating n‐3 and n‐6 fatty acids were measured at baseline and after 4, 8, and 12 weeks of diet exposure. Results: All 82 randomized participants were included in biochemical analyses. Seventy participants completed at least 2 EMA surveys and were included in primary EMA analyses. Variability in mood, energy, irritability, and pain as measured using EMA was reduced in the H3‐L6 group compared to the CD group. No significant differences in mean ratings of mood symptoms, or any other symptom measures, were detected. The dietary intervention effect on target PUFAs significantly differed by the group over time. Conclusions: A dietary intervention adjunctive to usual care showed preliminary efficacy in improving variability in mood symptoms in participants with BD. Trial Registration : ClinicalTrials.Gov NCT02272010.